Research of Data Mining Algorithm Based on Cloud Database (Global Journal of Computer Science and Technology, 2014)
There is an immense amount of data in the cloud database and among these data, much potential and valuable knowledge are implicit. The key point is to discover and pick out the useful knowledge, and to do so automatically. In this paper, the data model of the cloud database is analyzed. Through analyzing and classifying, the common features of the data are extracted to form a feature data set. The relationships among different areas in the data are then analyzed, from which the new knowledge can be found. In the paper, the basic data mining model based on the cloud database is defined, and the discovery algorithm is presented.
Keywords: cloud database; data mining; association rules; classification characteristic